PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA ASN KANTOR KEMENAG KABUPATEN SITUBONDO - Rahman S, Firman Fathor; Karnadi, Karnadi; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2022)
An agency requires good and appropriate management so that employees can achieve effective, efficient and optimal work results, especially at the Office of the Ministry of Religion of Situbondo Regency. The purpose of this study was to analyze and examine the effect of the work environment and organizational culture on organizational citizenship behavior through job satisfaction as an intervening variable in the state civil apparatus. This research is an explanatory research. The population in this study is the State Civil Apparatus of the Ministry of Religion of Situbondo Regency. The sampling technique was determined by quota sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that the work environment has a significant effect on job satisfaction, organizational culture has a significant effect on job satisfaction, the work environment has a positive but not significant effect on job satisfaction. organization citizenship behavior, organizational culture has a significant effect on organizational citizenship behavior, job satisfaction has a significant effect on organizational citizenship behavior. The results of the indirect hypothesis test indicate that the work environment variable on organizational citizenship behavior through job satisfaction has a significant positive effect, organizational culture on organizational citizenship behavior has a significant positive effect.